Contribution of Clinically Derived Mutations in ERG11 to Azole Resistance in Candida albicans - Flowers, Stephanie A. (Antimicrob Agents Chemother, 2014)
In Candida albicans, the ERG11 gene encodes lanosterol demethylase, the target of the azole antifungals. Mutations in ERG11 that result in an amino acid substitution alter the abilities of the azoles to bind to and inhibit Erg11, resulting in resistance. Although ERG11 mutations have been observed in clinical isolates, the specific contributions of individual ERG11 mutations to azole resistance in C. albicans have not been widely explored. We sequenced ERG11 in 63 fluconazole (FLC)-resistant clinical isolates. Fifty-five isolates carried at least one mutation in ERG11, and we observed 26 distinct positions in which amino acid substitutions occurred. We mapped the 26 distinct variant positions in these alleles to four regions in the predicted structure for Erg11, including its predicted catalytic site, extended fungus-specific external loop, proximal surface, and proximal surface-to-heme region. In total, 31 distinct ERG11 alleles were recovered, with 10 ERG11 alleles containing a single amino acid substitution. We then characterized 19 distinct ERG11 alleles by introducing them into the wild-type azole-susceptible C. albicans SC5314 strain and testing them for susceptibilities to FLC, itraconazole (ITC), and voriconazole (VRC). The strains that were homozygous for the single amino acid substitutions Y132F, K143R, F145L, S405F, D446E, G448E, F449V, G450E, and G464S had a ≥4-fold increase in FLC MIC. The strains that were homozygous for several double amino acid substitutions had decreased azole susceptibilities beyond those conferred by any single amino acid substitution. These findings indicate that mutations in ERG11 are prevalent among azole-resistant clinical isolates and that most mutations result in appreciable changes in FLC and VRC susceptibilities.